Genetic markers and predictive model for individual differences in countermovement jump enhancement after resistance training - Mei, Tao; Li, Xiaoxia; Li, Yanchun; Yang, Xiaolin; Li, Liang; He, Zihong (Biology of Sport, 2024)
This study aims to utilize Genome-Wide Association Analysis (GWAS) to identify genetic markers associated with enhanced power resulting from resistance training. Additionally, we analyze the potential biological effects of these markers and establish a predictive model for training outcomes. 193 Han Chinese adults (age: 20±1 years) underwent resistance training involving squats and bench presses at 70% 1RM, twice weekly, 5 sets×10 repetitions, for 12 weeks. Whole-genome genotyping was conducted, and participants’ countermovement jump (CMJ) height, lower limb muscle strength, and body muscle mass were assessed. CMJ height change was used to assess changes in power and subjected to Genome-Wide Association Analysis (GWAS) against genotypes. Employing Polygenic Score (PGS) calculations and stepwise linear regression, a predictive model for training effects was constructed. The results revealed a significant increase in CMJ height among participants following the resistance training intervention (Δ% = 16.53%, p < 0.01), with individual differences ranging from -35.90% to 125.71%. 38 lead SNPs, including PCTP rs9907859 ( p < 1 ×10 −8 ), showed significant associations with the percentage change in CMJ height after training (p < 1×10 −5 ). The explanatory power of the predictive model for training outcomes, established using PGS and phenotypic indicators, was 62.6%, comprising 13.0% from PGS and 49.6% from phenotypic indicators. SNPs associated with power resistance training were found to participate in the biological processes of musculoskeletal movement and the Striated muscle contraction pathway. These findings indicate that individual differences in the training effect of CMJ exist after resistance training, partially explained by genetic markers and phenotypic indicators (62.6%).